Haribhajana Siṅgha-kāwi : thīma-wigiānaka adhiaina : Nā dhuppe nā chāweṃ, Saṛaka de safe ute ādhārita - Haracarana Kaura (Nawacetana Pabalisharaza, 1980)
Thematic study of the poetry of Haribhajan Singh, b. 1920, Panjabi litterateur.